Quramalı kórsetkishli- dárejeli teńlemelerdi sheshiw usılları (ILIM hám JÁMIYET, 2024)
The article contains examples and problems that will further increase students‘ interest in mathematics. These examples and tasks are of great importance in the formation of their knowledge and skills. It is very important to increase the interest of students interested in mathematics and teach them to solve logical problems.